Efficacy of phosphate solubilizing Actinobacteria to improve rock phosphate agronomic effectiveness and plant growth promotion - Soumare, Abdoulaye; Boubekri, Kenza; Lyamlouli, Karim; Hafidi, Mohamed; Ouhdouch, Yedir; Kouisni, Lamfeddal (Rhizosphere, 2021)
In the rhizosphere, plant growth is facilitated by plant-growth-promoting rhizobacteria (PGPR). PGPRs like Actinobacteria can increase level of phosphate available to plants through P solubilization or mineralization. In this study we evaluated the ability of nine Phosphate Solubilizing Actinobacteria (PSA) to release P from rock phosphate (RP) and to promote maize growth and yield under in vitro and greenhouse conditions. Plate bioassay and pots culture experiment were conducted to investigate the effects of these PSA on maize plants development. High reactive rock phosphate (BG4, from Gantour phosphate mine, Morocco) and triple superphosphate (TSP) from Morocco were used as positive controls. BG4, is a reactive RP directly used to increase the P status of soil according to the Office Chérifien des Phosphates (OCP). For the other treatments, plants were grown in soil amended with low reactive RP obtained from the Khouribga phosphate mine (Morocco) and inoculated with selected PSA strains. Our findings have indicated that, PSA inoculation resulted in increasing of the assessed growth parameters and nutrient content in maize seedlings. Four of the tested strains (BC3, BC10, BC11 and P18) showed high performance efficiency in RP-solubilization and improved plant P nutrition and growth under low-P conditions i.e. amended with low reactive RP. Furthermore, inoculation with these latter strains also showed an important production of acid and alkaline phosphatase in the rhizosphere of the maize. The relative agronomic effectiveness (RAE) index showed that BC3(Streptomyces griseorubens) and BC11 (Norcardiopsis alba) increased the yield by 135.33 and 126.91% over the positive controls BG4. These strains can be considered as the most efficient to use rock phosphate as a crude phosphate fertilizer. Overall, our results demonstrate that PSA could constitute a promising solution to valorize low reactive RP in agriculture. The 16 S rRNA gene sequencing and phylogenetic analysis identified these isolates belong to Streptomyces and Nocardiopsis genera. •Actinobacteria increase the agronomic effectiveness of low reactive RP for direct application.•Two strains BC3 and BC11 combined with RP showed a performance equivalent to that of fertilization with TSP.•Actinobacteria combined with Rp is a sustainable biofertilizer that may reduce dependency on agrochemicals without yield lost.